A pore-scale study on the dynamics of spontaneous imbibition for heterogeneous sandstone gas reservoirs - Wang, Mingchuan; Wang, Ran; Yuan, Shuai; Zhou, Fujian (Frontiers in Energy Research, 2023)
The underlying mechanism for spontaneous imbibition in water-gas system plays a significant role for hydraulic fracturing in tight gas reservoirs. The objective of this study is to characterize the heterogeneity of tight sandstones and investigate its effects on spontaneous imbibition from the perspective of pore scale. We select different cores varying from pore structure and heterogeneity to evaluate their impacts on the dynamics of spontaneous imbibition. The heterogeneities of tight cores are characterized by CT scans. Results show that clay minerals have higher CT numbers than core matrix, and micropores are mainly distributed in the clay particles rather than in the core matrix. Additionally, water imbibition rate of micropores is larger than macropores, and water is imbibed more with the decrease of permeability when the porosities are similar. Moreover, the results of 1D frequency scans show that water distribution in different positions of cores is governed by the distribution of clay particles. These findings can help us to further understand the distribution of fracturing fluid in the heterogeneous tight sandstone reservoirs.